How to be Married - Williams, Polly (London Headline Review, 2010)
Sadie Drew thinks she must be the world$1 (Bs worst wife. She only needs to walk into a room to make it untidy. She wears flannel pyjamas in bed. Furry things breed in her fridge. But she$1 (Bs a busy working mother not a wifebot and husband Tom loves her as she is. Until he gets a hot new job and things change. There are alpha-wives to entertain. Nuclear rows. Unsettling secrets. And the smell of another woman$1 (Bs perfume on his suit. Sadie risks losing everything if she can$1 (Bt transform herself into the perfect wife... But what is a perfect wife anyway?s
English Fiction.
Keywords: Marriage -- Wives -- Wives--Psychology